The Effect of Corporate Social Responsibility and Capital Structure on the Financial Performance of Mining Companies Listed on the Indonesian Stock Exchange (IDX) - Nuralfania; Masdar Mas’ud; Budiandriani; Syamrul (SEAN Institute, 2026)
This study aims to analyze the effects of corporate social responsibility (CSR) and capital structure on the financial performance of mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employs a quantitative approach using purposive sampling. From a population of 67 companies, 6 companies were selected as the research sample. The data were analyzed using multiple linear regression with the aid of IBM SPSS. The results indicate that CSR and capital structure have a positive and significant effect on financial performance. These findings suggest that enhancing CSR implementation and optimizing capital structure management can support improvements in a company’s financial performance.